Ju Re Ba Du therapy for Postherpetic neuralgia: A protocol for systematic review and meta-analysis. Issue 44 (30th October 2020) - Huang, Shijie; Pan, Zhengqi; Li, Zimeng; Zhu, Xinyun; Ma, Tingting; Wu, Jie
Abstract: Introduction: Postherpetic neuralgia (PHN) is one of the most common types of chronic neuropathic pain, which seriously affects quality of the life because of pain severity and poor response to the currently available treatments. Ju Re Ba Du therapy as a form of acupuncture therapy which is proved to be effective in RCTs and very suitable for patients, has been used in Postherpetic neuralgia in patients for a long time, therefore a systematic review is necessary to provide available evidence for further study. Methods and analysis: The following databases will be searched from their inception to October 2020: Electronic database includes PubMed, Embase, Cochrane Library, Web of Science, Nature, Science online, VIP medicine information, and CNKI (China National Knowledge Infrastructure). Primary outcome: pain intensity assessed on a visual analogue scale (VAS); Additional outcomes: Quality of life assessed by the 36-Item Short-Form Health Survey (SF-36); Self-Rating Anxiety Scale (SAS); Self-Rating Depression Scale (SDS); Sleep quality measured by the Pittsburgh Sleep Quality Index (PSQI). Data will be extracted by two researchers independently, risk of bias of the meta-analysis will be evaluated based on the Cochrane Handbook for Systematic Reviews of Interventions. All data analysis will be conducted by data statistics software Review Manager V.5.3. and Stata V.12.0. Results: The results of this study will systematically evaluate the effectiveness and safety of Ju Re Ba Du therapy intervention for people with Postherpetic neuralgia. Conclusion: The systematic review of this study will summarize the current published evidence of Ju Re Ba Du therapy for the treatment of Postherpetic neuralgia, which can further guide the promotion and application of it. Ethics and dissemination: This study is a systematic review, the outcomes are based on the published evidence, so examination and agreement by the ethics committee are not required in this study. We intend to publish the study results in a journal or conference presentations. OSF registration number: September 29, 2020 osf.io/r6y9b. (https://osf.io/r6y9b )